2019
DOI: 10.14202/vetworld.2019.925-931
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence, characterization, and antibiogram of Staphylococcus aureus in meat, meat products, and some seafood from Libyan retail markets

Abstract: Aim: The aim of the current investigation was to screen the presence of Staphylococci spp., especially S. aureus in meat, meat products of different animal species, and some seafood sold in some retail markets in Libya using cultural and molecular techniques, and to study their antibiotics resistance profiles. Materials and Methods: A total of 139 samples from red meat, meat products, and seafood were collected from many areas in Libya. Enumeration and isolation of Staphylococci spp. and S. aureus by normal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
15
5
2

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 37 publications
5
15
5
2
Order By: Relevance
“…In another studies, Naas et al [5] showed that six (6) S. aureus isolates were resistant to Clindamycin (100%), tobramycin (50%), Erytromycin (50%), Gentamycin (50%), Penicillin (50%) and tetracyclin (66%) while no resistant strains were detected with trimethoprim + sulfamethoxasole (0%) and Vancomycin (0%). Tassew et al [25] and Waters et al [26] reported high resistance to erythromycin, tetracycline, penicillin in a ratio ranged from 66% to 85%.…”
Section: Antibiogram Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…In another studies, Naas et al [5] showed that six (6) S. aureus isolates were resistant to Clindamycin (100%), tobramycin (50%), Erytromycin (50%), Gentamycin (50%), Penicillin (50%) and tetracyclin (66%) while no resistant strains were detected with trimethoprim + sulfamethoxasole (0%) and Vancomycin (0%). Tassew et al [25] and Waters et al [26] reported high resistance to erythromycin, tetracycline, penicillin in a ratio ranged from 66% to 85%.…”
Section: Antibiogram Resultsmentioning
confidence: 97%
“…Moreover, the resistance to minocyclin is not surprising because cyclin family is one of the most commonly used antibiotics in Abidjan livestock production systems. In addition, resistance to Vancomycin seems to be low in many reported studies [5]. The difference in the percentage of antibiotic susceptibility may be due to the type of antibiotic used in farming sector or due to local S. aureus strains to each country [5,28].…”
Section: Antibiogram Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The presence of S. aureus on the meat samples (36%) indicates that unhygienic practices and thus cross-contamination occurred onto the meat from the hide and/ or from the meat handlers. Ultimately, the presence of S. aureus on raw meat is indicative of poor hygiene conditions in the food chain, mainly due to contamination by food handlers and equipment ( Naas et al, 2019 ). The detection of E. coli and S. aureus from the meat samples was expected and the frequency of isolation is similar to those found by Schlegelová et al (2004) , who detected E. coli and S. aureus in meat samples of beef in a slaughterhouse in 67% and 24% of samples, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Incidence of S. aureus in meat products in Iran [18], China [19], India [20], USA [21], Iraq [22], and Nigeria [23] were 9.86%, 35%, 21.81%, 27.90%, 54.20%, and 9.70%, respectively. Total incidence of S. aureus amongst the beef, camel meat, chicken, mutton, beef burger, beef sausage, ground beef, chicken burger, ground chicken, and chicken sausage samples collected from Libya were 20%, 23.80%, 40%, 0%, 25%, 33%, 36.40%, 50%, 20%, and 10%, respectively [24]. Brazilian survey [25] revealed that the incidence of S. aureus amongst the beef burger, beef sandwich, chicken burger and chicken sandwich samples were 64%, 20%, 72% and 8%, respectively.…”
Section: Discussionmentioning
confidence: 99%